ANALISIS KINERJA KEUANGAN PERUSAHAAN SEPENINGGAL PENDIRI PERUSAHAAN (Studi Kasus pada PT Sri Rejeki Isman Tbk di Sukoharjo) - Fadjar Harimurti, Vita Agustina, Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
This study aims to determine the difference in financial performance after the founding of the company. Types of data used in this study are Qualitative Data and Quantitative Data. Sources of data used in this study obtained from annual financial statements of PT Sri Rejeki Isman Tbk listed on the Indonesia Stock Exchange during the period 2011 - 2016 then analyzed by using the ratio of financial statements consisting of profitability ratios, liquidity ratios, and solvency. This research is descriptive research using case study method that compare company performance before and after death of company founder. The technique of data analysis using t-test of the corresponding sample. The result of research shows that: (1) profitability ratios consisting of ROA, ROE, earning power, and profit margin are no different, (2) liquidity ratio consisting of current ratio and acid test ratio there are difference, (3) solvency ratio of DR, and DER there is no difference. The ratio of profitability, liquidity and solvency when tested in parallel the results obtained there are differences.Keywords: Financial statements, financial ratios, financial performance